Individual Identification of Large Felids in Field Studies: Common Methods, Challenges, and Implications for Conservation Science - Pereira, Keren S.; Gibson, Luke; Biggs, Duan; Samarasinghe, Dinal; Braczkowski, Alexander R. (Frontiers in Ecology and Evolution, 2022)
Large felids represent some of the most threatened large mammals on earth, critical for both tourism economies and ecosystem function. Most populations are in a state of decline, and their monitoring and enumeration is therefore critical for conservation. This typically rests on the accurate identification of individuals within their populations. We review the most common and current survey methods used in individual identification studies of large felid ecology (body mass >25 kg). Remote camera trap photography is the most extensively used method to identify leopards, snow leopards, jaguars, tigers, and cheetahs which feature conspicuous and easily identifiable coat patterning. Direct photographic surveys and genetic sampling are commonly used for species that do not feature easily identifiable coat patterning such as lions. We also discuss the accompanying challenges encountered in several field studies, best practices that can help increase the precision and accuracy of identification and provide generalised ratings for the common survey methods used for individual identification.